2021
DOI: 10.21037/acs-2020-rp-21
|View full text |Cite
|
Sign up to set email alerts
|

Back to the root: a large animal model of the Ross procedure

Abstract: The excellent clinical outcome of the Ross procedure and previous histological studies suggest that the pulmonary autograft has the potential to offer young patients a permanent solution to aortic valve disease.We aim to study the early mechanobiological adaptation of the autograft. To this end, we have reviewed relevant existing animal models, including the canine models which enabled Donald N Ross to perform the first Ross procedure in a patient in 1967. Two research groups recently evaluated the isolated ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In a similar animal model using resorbable external support, 123). (123). Preliminary histological evaluation is consistent with previous clinical and experimental explant studies (Figure 6).…”
Section: Experimental Evidence For Autograft Remodelingsupporting
confidence: 87%
See 3 more Smart Citations
“…In a similar animal model using resorbable external support, 123). (123). Preliminary histological evaluation is consistent with previous clinical and experimental explant studies (Figure 6).…”
Section: Experimental Evidence For Autograft Remodelingsupporting
confidence: 87%
“…In vitro culture of a pulmonary artery in a bioreactor may provide valuable insights into the timeline of early remodeling and the role of shear stress, pre-stretch at implantation and acute hypertension. Large animal models also hold great promise to evaluate whether current strategies to prevent dilatation—external support and antihypertensive treatment—promote remodeling, either by modifying the mechanical environment or by interfering with molecular pathways ( 123 ). To assess whether the autograft remains viable—capable of healing and regulating its mechanical properties—active mechanical testing of freshly explanted leaflets and wall would be required ( 162 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a reduction in arterial wall dilation and therefore preservation of valve function, it turns out that a permanent textile wrapping can lead to excessive stress-shielding phenomena [11]. Experimental animal trials of a polymeric reinforcement around the autograft have shown thinning of the vessel wall, smooth muscle cell death, and loss of wall mechanical compliance [12,13,14]. A permanently present external support can prevent dilatation and tissue failure after surgery, but it inhibits important arterial wall compliance.…”
Section: Introductionmentioning
confidence: 99%